The handbook of translation and cognition - Schwieter, John W., 1979-; Ferreira, Aline (Hoboken, NJ : Wiley-Blackwell, 2017)
The Handbook of Translation and Cognition is a pioneering, state-of-the-art investigation of cognitive approaches to translation and interpreting studies (TIS).
Part I: Introduction -- Part II: Theoretical Advances -- Part III: Methodological Innovations -- Part IV: Translator and workplace characterisitcs -- Part V: Competence, training, and interpreting -- Part VI: Moving Forward.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Psycholinguistics -- Handbooks, manuals, etc; LANGUAGE ARTS & DISCIPLINES / General; Psycholinguistics; Handbooks and manuals; Electronic books